FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI RUMPUT LAUT PADA KELOMPOK TANI "MARIO MARENNU" DI DESA WEWANGRIU KECAMATAN MALILI KABUPATEN LUWU TIMUR - Rikmansyah Zakaria; Wulandari Dwi ER; Budiarto Budiarto (Jurnal Dinamika Sosial Ekonomi, 2015)
This study aims to (1) analyze the effect of input variables, wide area, TSP. ZA, EM4 fertilizer, labor and seeds to seaweed production at Farmers Group" Mario Marennu" (2) determine which variables ure dominant affect the production of seaweed on Farmers Group Mario Marennu Implementation of research methods used in this study is a survey method. Method of determining the location of the study using purposive. The method of sampling using census method. Kinds of data used is primary data and secondary data Sources of data obtained seaweed farmers, village office, district office, department of fisheries, gapoktan office and library research. Data collection techniques by observation, questionnaires, interviews and documentation studies. To analyze the factors of production of seaweed on Cobb Douglas production function and optimization. Research results are land area, TSP fertilizer, ZA fertilizer, EM4 fertilizer, labor, and seeds to give positive effect on the production of seaweed While the individual affected the discharge area of the seed production. TSP, ZA fertilizer and use of seaweed. The use of factors of production of seaweed on Farmers Group "Mario Marennu "not optimal.Keywords: Factor of Production. Production, Optimization and Seaweed